Pentoxifylline and propentofylline prevent proliferation and activation of the mammalian target of rapamycin and mitogen activated protein kinase in cultured spinal astrocytes. Issue 2 (27th November 2012) - Norsted Gregory, Ebba; Delaney, Ada; AbdelMoaty, Sally; Bas, Duygu B.; Codeluppi, Simone; Wigerblad, Gustaf; Svensson, Camilla I.
Abstract Astrocyte activation is an important feature in many disorders of the central nervous system, including chronic pain conditions. Activation of astrocytes is characterized by a change in morphology, including hypertrophy and increased size of processes, proliferation, and an increased production of proinflammatory mediators. The xanthine derivatives pentoxifylline and propentofylline are commonly used experimentally as glial inhibitors. These compounds are generally believed to attenuate glial activity by raising cyclic AMP (cAMP) levels and inhibiting glial tumor necrosis factor (TNF) production. In the present study, we show that these substances inhibit TNF and serum‐induced astrocyte proliferation and signaling through the mammalian target of rapamycin (mTOR) pathway, demonstrated by decreased levels of phosphorylated S6 kinase (S6K), commonly used as a marker of mTOR complex (mTORC) activation. Furthermore, we show that pentoxifylline and propentofylline also inhibit JNK and p38, but not ERK, activation induced by TNF. In addition, the JNK antagonist SP600125, but not the p38 inhibitor SB203580, prevents TNF‐induced activation of S6 kinase, suggesting that pentoxifylline and propentofylline may regulate mTORC activity in spinal astrocytes partially through inhibition of the JNK pathway. Our results suggest that pentoxifylline and propentofylline inhibit astrocyte activity in a broad fashion by attenuating flux through specific pathways. © 2012 Wiley Periodicals, Inc.